In an AP,the sum of first n term is 3n2/2+13n/2

find its 25th term

 n =1

S1 = 3/2+13/2 = 16/2 =8

S2 = 12/2 + 26/2 = 6+13 = 19

S2 -S1= 19-8 = 11=a2

a2-a1 =d 

d= 11 -8 = 3

a25 = a+(25-1)d

        = 8 + (24 x3)

         = 72+8 =80

  • 95
why u r taking nth value 1 4 thiz question
  • -4
hw thiz answer
 
  • -3
komal singh wrong answer
 
  • -7
actually here n is substituted as 1
  • 0
you have solved this sum in such a simple way ;)
thankyou so much ^-^
  • -4
who the hell told this ans is wrong
this is the right ans
 
  • -3
komal answer is write
thank you^_^
  • -2
First of all don;t get annoyed .
Komal Singh you first substituted n with 1 .OK I got that .
Then you found out the second term by S2-S1. FINE I got that too,
Then you went on to find (d) but then before you have written that S1=8 but then you also have written that a1 is also=8.
How can the answer be correct?
 
  • -3
For me 1 doubt how we want to do S2
  • -5
How did komal singh got n is 1. Explain it to me
  • -2
How did a came to be 8
  • -5
http://www. meritnation.com/ ask-answer/ question/ in-an-ap-the-sum-of -first-n-terms-is- given-by-sn- 3n2-2-5/math/3708981. Use this link. Here the expert gave the correct answer as 76
  • 6
Answer for👆

  • 13
By mistake I typed sorry .similar question number alone different .👆

  • 1
Answer👆
  • -1
Answer 👆

  • 30
ans is 80 only
  • -6
hope it helps

  • 19
i think so answer is=76
  • -2
No correct answer is 80 Which is in up [1st] Whereas you are confusing with another similar question
  • -2
Is this helpful for you

  • 3
Sum of first n terms = 3n²/2 + 13n/2
As we know that nth term = (Sum of nth term ) - ( sum of (n-1)th term),
so
25th term = (sum of 25 terms) - ( sum of 24 terms)
                        =(3×(25)²/2 +(13×25)/2) - ( 3×(24)²/2 + (13×24)/2)
                        = 1100 - 1020
                        = 80
  • 2
OMG so confusing answers
  • -1
the answer is 23 764
  • -1
Komal your answer is in correct
  • -2
The correct ans for this question is 80

  • 0
From best refreshee

  • 0
n =1 S1 = 3/2+13/2 = 16/2 =8 S2 = 12/2 + 26/2 = 6+13 = 19 S2 -S1= 19-8 = 11=a2 a2-a1 =d d= 11 -8 = 3 a25 = a+(25-1)d = 8 + (24 x3) = 72+8 =80
  • -2
Answer of above question is following

  • 0
What are you looking for?